2008
DOI: 10.1002/adma.200801322
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Living Light‐Emitting Electrochemical Cells – Control through Supramolecular Interactions

Abstract: Light‐emitting electrochemical cells with lifetimes surpassing 3000 hours at an average luminance of 200 cd m−2 are obtained with an ionic iridium(III) complex conveniently designed to form a supramolecularly caged structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
210
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(228 citation statements)
references
References 28 publications
(41 reference statements)
11
210
1
6
Order By: Relevance
“…This interaction minimises the expansion of the metal-ligand bonds in the excited state and precludes the attack by water and other nucleophiles resulting in the long observed lifetimes. We concluded that analogous complexes with 6,6 0 -diphenyl-2,2 0 -bipyridine would have an even greater stabilisation of the excited state as the two pendant phenyl groups would stack with different ppy ligands giving a very ''tight'' complex.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This interaction minimises the expansion of the metal-ligand bonds in the excited state and precludes the attack by water and other nucleophiles resulting in the long observed lifetimes. We concluded that analogous complexes with 6,6 0 -diphenyl-2,2 0 -bipyridine would have an even greater stabilisation of the excited state as the two pendant phenyl groups would stack with different ppy ligands giving a very ''tight'' complex.…”
mentioning
confidence: 99%
“…[3][4][5] We have recently reported the use of intra-and intermolecular face-to-face p-stacking for the stabilisation of the ground and excited state of electroluminescent iridium complexes and shown that this leads to exceptionally long-living LEC devices. 6,7 The long lifetimes of these devices establish LECs as a viable alternative to OLED technology. In [Ir(ppy)(pbpy)] + (Hppy = 2-phenylpyridine, pbpy = 6-phenyl-2,2 0 -bipyridine) the pendant phenyl group of the pbpy ligand forms a face-to-face p-stack with the metallated ring of a ppy ligand (3.2-3.5 Å ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This ring is predisposed to form an intramolecular p-stacking interaction with the phenyl ring of one of the C^N ligands, enveloping the iridium core in a supramolecularly caged hydrophobic scaffold that shields it from adventitious attack from prospective nucleophiles in the device that degrade the emitter [14,61,62]. This substitution pattern is more common for six-membered ring systems, such as the ligand 6-phenyl-2,2 0 -bipyridine (see Sect.…”
Section: Stabilitymentioning
confidence: 99%
“…1,31,32 Especially high brightness and long operation lifetime seem to be hard to unite: most devices with high brightness are short-lived and vice versa. 16,27,29 On the other hand, the discovery of stable, yellow iTMC-complex due to intramolecular π−π stacking interactions 33 and pulsed operation mode yielded devices with lifetimes exceeding 4000 h at maximum luminance over 650 cd/m 2 and subsecond turn-on times. 17 Recently, the approach of multiple π-stacking interactions yielded promising results also for red-emitting complexes, 18 making the iTMC-LECs together with their simple architecture very attractive for industrial roll-to-roll fabrication.…”
Section: ■ Introductionmentioning
confidence: 99%